The Analysis of Greenfield FDI and Economic Growth in Western Balkans and Visegrad States - Ercegovac, Dajana; Beker Pucar, Emilija (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2023)
The aim of this research is to identify a correlation link between Greenfield FDI inflows and GDP growth rate in Western Balkan countries compared to the Visegrad States in order to give relevant implications towards sustainable economic development in less developed countries of Western Balkans. The authors present descriptive analysis together with correlation analysis for the Western Balkans and the Visegrad States in the time period 2003-2020. This research analyzes data in regard to the structural break of the Global Financial Crisis and pandemic of corona virus. Government recommendations are directed in further improvements in the quality of public institutions, incentive measures and investment environment in order to attract favorable greenfield FDI investments and accelerate real convergence towards developed European economies.